2007
DOI: 10.1007/s00411-007-0130-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the radiation risk due to environmental contamination by 241Am from lightning rods disposed at uncontrolled garbage dumps

Abstract: Radioactive lightning rods were manufactured in Brazil until 1989, when the licenses for using radioactive sources in these products were lifted by the national nuclear authority. Since then, these rods have been replaced by the Franklin type and collected as radioactive waste. However, only 20% of the estimated total number of installed rods has been delivered to the Brazilian Nuclear Commission. This situation causes concern, since there is the possibility of the rods to be disposed as domestic waste. In Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…As reported previously (Marumo et al 2008), the release of 241 Am was not constant, the initial amount of americium being relatively large, followed by a more constant longterm release. Figure 1 shows the average values obtained from the three lysimeters.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…As reported previously (Marumo et al 2008), the release of 241 Am was not constant, the initial amount of americium being relatively large, followed by a more constant longterm release. Figure 1 shows the average values obtained from the three lysimeters.…”
Section: Resultsmentioning
confidence: 53%
“…However, only 20% of the estimated total number of installed rods was delivered to the Brazilian Nuclear Energy Commission. An assessment of the risk of contamination by 241 Am used in lightning rods discarded as domestic waste was recently published (Marumo et al 2008). In that study, the radionuclide was placed in a lysimeter filled with organic waste from a restaurant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms can play a pivotal role in changing 241 Am(III) solubility and efficient biosorption by E.coli, a marine bacterium, Rhizopus arrhizus, and Candida utilis [51][52][53][54]. In particular, Marumo et al reported the new radionuclides-tolerant bacterial strains such as Flavobacterium spp., Pseudomonas gladioli, Chryseobacterium indologenes and Ochrobactrum anthropi, which have an influence on the microbial community responsible for the degradation processes of organic waste [55,56].…”
Section: Characteristics Of Americium and Microbial Interactionsmentioning
confidence: 99%